1985
DOI: 10.1177/002221948501800808
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Control Factors in Search Performance of Hyperactive Children

Abstract: Added stimulation, both biochemical and environmental, has been used to improve the sustained attention but less frequently the search-attention performance of hyperactive children. In the present study a search task was used that differed from sustained-attention tasks only in an additional requirement for visual scanning. The performance of hyperactive and control children on a noncolored version of this task was compared with a version to which color stimulation had been presented that reduced the area to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…This suggests that over time, adaptation may occur, and that the novelty of color wears off and no longer serves to increase stimulation. Extending these results to a search-attention task involving visual scanning, a study by Zentall (1985) found equivalent results to those found for sustained attention tasks. That is, the performance of hyperactive children was normalized during color conditions, especially during the first two-thirds of task performance.…”
Section: Within-task Stimulationmentioning
confidence: 56%
See 1 more Smart Citation
“…This suggests that over time, adaptation may occur, and that the novelty of color wears off and no longer serves to increase stimulation. Extending these results to a search-attention task involving visual scanning, a study by Zentall (1985) found equivalent results to those found for sustained attention tasks. That is, the performance of hyperactive children was normalized during color conditions, especially during the first two-thirds of task performance.…”
Section: Within-task Stimulationmentioning
confidence: 56%
“…Some studies required only that participants surpass a cut-off score on the Conner's Behavior Rating Scale teacher version (e.g., Ajibola and Clement, 1995;Belfiore et al, 1996;Fitzgerald et al, 1986;Zentall, 1985) or another teacher report measure (e.g., Robinson et al, 1981;Zentall, 1986). This is not consistent with best practices for diagnosing ADHD, which include the integration of reports from multiple individuals in more than one setting (Barkley, 1998).…”
Section: Limitations Of Current Research and Future Directionsmentioning
confidence: 99%
“…Thus, their sustained attentional "deficit" is related to the length, familiarity, or repetitiveness of the task. While performing these tasks, students with ADHD look around or change their attentional focus more often than their peers, especially during later performance (e.g., Zentall, 1985Zentall, , 1986Zentall & Zentall, 1976;Zentall, Falkenberg, & Smith, 1985).…”
Section: Sustained Inattentionmentioning
confidence: 99%
“…These techniques are typically used by general and special educators, who provide direct services to children with ADHD-I and -C. For improvements in sustained attention (i.e., after the child has mastered the selective-attention requirements of the task), added novelty (relevant or nonrelevant) has been documented to improve the sustained attention of students with ADHD more than for matched comparisons when it is placed (a) prior to a visual creativity task (i.e., an exciting car-chase video: Shaw & Brown, 1999) and (b) within a task (color added to search, sustained attention, handwriting, copying, or matching-figures tasks : Imhof, 2004;Lee & Asplen, in press;Zentall, 1985Zentall, , 1986Zentall & Dwyer, 1988;Zentall et al, 1985). That is, even nonrelevant color can produce normalized performance for students with ADHD during sustained-attention tasks, which is similar to the effects obtained by psychostimulant medication (i.e., improved behavior, attention, and productivity and reduced careless errors).…”
Section: Sustained Inattentionmentioning
confidence: 99%
“…The reprimand is short and to the point. For parents who like to lecture, it helps to know that for ADHD children extra narrative and detail can reduce comprehension and performance (Edmonds & Smith, 1985;Shroyer & Zentall, 1986), and the children pay attention less to long tasks (Zentall, 1985;Zentall & Zentall, 1976). The child's attention skills and angry emotional behavior associated with disruptive defiance is incompatible with the skills necessary to comprehend and respond effectively to long parent explanation.…”
Section: Step 4 Praisementioning
confidence: 99%